Imaging predictors of treatment outcomes in rectal cancer: An overview. (September 2018) - Mahadevan, Lakshmi Shree; Zhong, Jim; Venkatesulu, BhanuPrasad; Kaur, Harmeet; Bhide, Shreerang; Minsky, Bruce; Chu, William; Intven, Martijn; van der Heide, Uulke A.; van Triest, Baukelien; Krishnan, Sunil; Hall, William A.
Abstract: The treatment protocols for rectal cancer continue to evolve, with increasing acceptance of a watch-and-wait policy for clinical complete responders to neoadjuvant chemoradiation therapy. It still, however, remains unclear who is likely to achieve a pathological complete response, which unequivocally portends a very favorable overall prognosis. Evolution of modern imaging techniques has paved the way for potential prediction of treatment response based on baseline, on-treatment, early post-treatment and subsequent follow-up imaging alone. Independent of tumor grade and stage, tumor marker levels, tumor size, radiation dose and fractionation, chemotherapy regimen, and extent/type of surgery, imaging biomarkers like circumferential resection margin (CRM), extramural venous space invasion (EMVI), imaging-based tumor regression grade, perfusion/diffusion-based functional imaging parameters, and imaging-based metabolic response have the ability to predict the likelihood of local recurrence and/or distant metastases. Textural features of images can add a further dimension to the predictive power of imaging. Finally, integration of genomic data with imaging biomarkers can potentially discern molecular mechanisms associated with distinct radiographic attributes of tumors. In this review, we evaluate and summarize the evidence to date of each imaging modality as a biomarker and its contribution to personalized decision making in rectal cancer.